Multivariate Analysis of Determinant Factors of The Decision to Provide Exclusive Breastfeeding in The Working Area of The Genuk Public Health Center in Semarang City - Agustin Nur Hidayah; Nurjanah Nurjanah; Enny Rachmani (East Asian Journal of Multidisciplinary Research, 2026)
This study aims to analyze the determinants of the decision to provide exclusive breastfeeding in the working area of ​​the Genuk Community Health Center in Semarang City. The study used a quantitative analytical design with a cross-sectional approach. The study sample consisted of 89 mothers with babies aged 6–12 months with a total sampling technique. Data analysis was performed using the Chi-Square test and multiple logistic regression. The results showed that 76.4% of respondents provided exclusive breastfeeding. Bivariate analysis showed that support from health workers (p=0.024), husband's support (p=0.023), and maternal stress levels (p=0.045) were significantly associated with exclusive breastfeeding. Multivariate analysis showed that husband's support was the most dominant factor (Exp(B)=2.432), followed by support from health workers and socioeconomic factors. It was concluded that increased husband support, the role of health workers, and socio-economic conditions contributed to the success of exclusive breastfeeding.